Migratory bird species benefit from traditional agricultural gardens in arid South Sinai - Norfolk, Olivia; Power, Andrew; Eichhorn, Markus P.; Gilbert, Francis (Elsevier, 2015)
In temperate and tropical regions agricultural conversion of natural habitat typically has negative impacts upon the diversity and functional complexity of bird communities. In arid environments however, the irrigation associated with agricultural can lead to an increase in local abundances of plant and insect resources, so has the potential to benefit bird communities. South Sinai is a key migratory corridor for many birds making the annual journey from wintering sites in Africa to breeding sites in Europe. We assess the importance of traditional Bedouin agricultural gardens for both resident and migratory species by comparing the density and functional composition of birds within the irrigated gardens to those in the unmanaged desert habitat. Estimated bird densities were significantly higher within the gardens than the unmanaged habitat, with a higher estimated species richness within the gardens. Functional composition of bird communities differed between the two habitats, with gardens supporting a higher proportion of insectivorous and migratory birds in addition to the resident desert species that were associated with the unmanaged habitat. Migratory species were almost entirely absent from the unmanaged habitat, suggesting that this region may not be used as a migratory stop-off if not for the presence of traditional agricultural gardens.